2019
DOI: 10.3390/app9235067
|View full text |Cite
|
Sign up to set email alerts
|

Phase Balancing and Reactive Power Support Services for Microgrids

Abstract: Alternating current (AC) microgrids are expected to operate as active components within smart distribution grids in the near future. The high penetration of intermittent renewable energy sources and the rapid electrification of the thermal and transportation sectors pose serious challenges that must be addressed by modern distribution system operators. Hence, new solutions should be developed to overcome these issues. Microgrids can be considered as a great candidate for the provision of ancillary services sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…In addition, the MODBUS protocol could also read data on the network (voltages, currents, powers, phases, total harmonic distortion (THD), etc.). Starting from formula (19), the THD is here calculated based on another equivalent consecrated formula (44), where the current was measured and I RMS easily computed, and the fundamental harmonic was calculated using Fast Fourier Transform (FFT).…”
Section: Power Factor Compensation Equipmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the MODBUS protocol could also read data on the network (voltages, currents, powers, phases, total harmonic distortion (THD), etc.). Starting from formula (19), the THD is here calculated based on another equivalent consecrated formula (44), where the current was measured and I RMS easily computed, and the fundamental harmonic was calculated using Fast Fourier Transform (FFT).…”
Section: Power Factor Compensation Equipmentmentioning
confidence: 99%
“…In the context of increasing the penetration of the intermittent renewable energy sources, the concept of microgrids (MG) becomes more frequent as a solution to these issues. There are efforts being made to improve the solutions available to microgrid developers in order to compensate the power factor and the load asymmetries inside the microgrid by utilizing advanced functionalities enabled by grid tied inverters of photovoltaics and energy storage systems [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the AC source should not generate the pulsating current due to the safety and lifetime procedures, the sinusoidal current waveform is just allowed to be injected to the grid according to power quality standards. Therefore, the non-linearity components of the required current are supplied by the AFP [15][16][17][18]. In order to decrease the output voltage ripples using only passive filters, the switching frequency is increased, which results in incremental switching losses a reduction in the system's efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the load-sharing experiment of the power converter with the proposed communication hardware confirmed that a stable parallel operation was performed. Figure 1 shows the equivalent circuit for analyzing the power-sharing characteristics of n parallel connected power converters [15]. In Figure 1, V 1 to V n are the initial setting output voltage of number of n power converters, with each power converter having the same value.…”
Section: Introductionmentioning
confidence: 99%